Comparative chloroplast genomes: insights into the evolution of the chloroplast genome of Camellia sinensis and the phylogeny of Camellia - Li, Li (BMC Genomics, 2021)
BACKGROUND: Chloroplast genome resources can provide useful information for the evolution of plant species. Tea plant (Camellia sinensis) is among the most economically valuable member of Camellia. Here, we determined the chloroplast genome of the first natural triploid Chinary type tea (‘Wuyi narcissus’ cultivar of Camellia sinensis var. sinensis, CWN) and conducted the genome comparison with the diploid Chinary type tea (Camellia sinensis var. sinensis, CSS) and two types of diploid Assamica type teas (Camellia sinensis var. assamica: Chinese Assamica type tea, CSA and Indian Assamica type tea, CIA). Further, the evolutionary mechanism of the chloroplast genome of Camellia sinensis and the relationships of Camellia species based on chloroplast genome were discussed. RESULTS: Comparative analysis showed the evolutionary dynamics of chloroplast genome of Camellia sinensis were the repeats and insertion-deletions (indels), and distribution of the repeats, indels and substitutions were significantly correlated. Chinese tea and Indian tea had significant differences in the structural characteristic and the codon usage of the chloroplast genome. Analysis of sequence characterized amplified region (SCAR) using sequences of the intergenic spacers (trnE/trnT) showed none of 292 different Camellia sinensis cultivars had similar sequence characteristic to triploid CWN, but the other four Camellia species did. Estimations of the divergence time showed that CIA diverged from the common ancestor of two Assamica type teas about 6.2 Mya (CI: 4.4–8.1 Mya). CSS and CSA diverged to each other about 0.8 Mya (CI: 0.4–1.5 Mya). Moreover, phylogenetic clustering was not exactly consistent with the current taxonomy of Camellia. CONCLUSIONS: The repeat-induced and indel-induced mutations were two important dynamics contributed to the diversification of the chloroplast genome in Camellia sinensis, which were not mutually exclusive. Chinese tea and Indian tea might have undergone different selection pressures. Chloroplast transfer occurred during the polyploid evolution in Camellia sinensis. In addition, our results supported the three different domestication origins of Chinary type tea, Chinese Assamica type tea and Indian Assamica type tea. And, the current classification of some Camellia species might need to be further discussed. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12864-021-07427-2.